DIFFERENT TECHNIQUES OF EXTRACTION AND ANTIVIRAL ACTIVITIES OF QUERCETIN AGAINST VIRUSES SUCH AS CORONAVIRUS, INFLUENZA VIRUS, EBOLA VIRUS, ZIKA VIRUS, AND OTHER VIRUSES - ABDESSEMED, DALILA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Quercetin (QCT) is a flavonoid, existed as a pigment in various plants. It is a bioactive compound that has a favorable effect on human health. Our work concerns the selection of different rapid techniques for QCT extraction, published on the different scientific databases, as ultrasound-assisted enzymatic extraction process, supercritical CO2 extraction, microwave-assisted extraction and consists of researching the antiviral activity of QCT and derivatives against viruses such as coronaviruses, influenza virus, human respiratory syncytial virus, Epstein-Barr virus gastric tumor, anti-hepatitis B virus, Zika virus, and Ebola. Following this research, we found that this molecule has a broad-spectrum antiviral activity. Is it effective in controlling this new form of coronavirus, this devastating virus, which currently affects thousands of people?